内容来源
B站视频BV1LC4y1P7gM
高斯积分
∫ 0 ∞ e − x 2 d x \int^\infty_0e^{-x^2}\mathcal{d}x ∫0∞e−x2dx
添加新元
设
f ( t ) = [ ∫ 0 t e − x 2 d x ] 2 f(t)=\left[\int^t_0e^{-x^2}\mathcal{d}x\right]^2 f(t)=[∫0te−x2dx]2
现目标
求
lim t → ∞ f ( t ) \sqrt{\lim_{t\rightarrow\infty}f(t)} t→∞limf(t)
对 f f f 求导
d f d t = 2 ∫ 0 t e − x 2 d x d d t ∫ 0 t e − x 2 d x = 2 e − t 2 ∫ 0 t e − x 2 d x = 2 ∫ 0 t e − ( x 2 + t 2 ) d x \begin{align*} \frac{\mathcal{d}f}{\mathcal{d}t}&= 2\int^t_0e^{-x^2}\mathcal{d}x\frac{\mathcal{d}}{\mathcal{d}t} \int^t_0e^{-x^2}\mathcal{d}x\\ &=2e^{-t^2}\int^t_0e^{-x^2}\mathcal{d}x\\ &=2\int^t_0e^{-(x^2+t^2)}\mathcal{d}x\\ \end{align*} dtdf=2∫0te−x2dxdtd∫0te−x2dx=2e−t2∫0te−x2dx=2∫0te−(x2+t2)dx
换元
设 y = x / t y=x/t y=x/t
那么
d x = t d y , y ∈ ( 0 , 1 ) \mathcal{d}x=t\mathcal{d}y,y\in(0,1) dx=tdy,y∈(0,1)
上式变为
2 ∫ 0 1 e − ( t 2 y 2 + t 2 ) t d y = − d d t ∫ 0 1 [ e − t 2 ( y 2 + 1 ) y 2 + 1 ] d y \begin{align*} &2\int^1_0e^{-(t^2y^2+t^2)}t\mathcal{d}y\\ &=-\frac{\mathcal{d}}{\mathcal{d}t} \int^1_0\left[\frac{e^{-t^2(y^2+1)}}{y^2+1}\right]\mathcal{d}y\\ \end{align*} 2∫01e−(t2y2+t2)tdy=−dtd∫01[y2+1e−t2(y2+1)]dy
所以
f ( t ) = − ∫ 0 1 [ e − t 2 ( y 2 + 1 ) y 2 + 1 ] d y + C f(t)=-\int^1_0\left[\frac{e^{-t^2(y^2+1)}}{y^2+1}\right]\mathcal{d}y+C f(t)=−∫01[y2+1e−t2(y2+1)]dy+C
现目标
求解 C C C
t → 0 t\rightarrow0 t→0
因为
lim t → 0 f ( t ) = lim t → 0 [ ∫ 0 t e − x 2 d x ] 2 = 0 \lim_{t\rightarrow0}f(t)= \lim_{t\rightarrow0} \left[\int^t_0e^{-x^2}\mathcal{d}x\right]^2=0 t→0limf(t)=t→0lim[∫0te−x2dx]2=0
所以
lim t → 0 f ( t ) = lim t → 0 − ∫ 0 1 [ e − t 2 ( y 2 + 1 ) y 2 + 1 ] d y + C = − ∫ 0 1 1 y 2 + 1 d y + C = − π 4 + C = 0 \begin{align*} \lim_{t\rightarrow0}f(t)&= \lim_{t\rightarrow0}-\int^1_0\left[\frac{e^{-t^2(y^2+1)}}{y^2+1}\right]\mathcal{d}y+C\\ &=-\int^1_0\frac{1}{y^2+1}\mathcal{d}y+C\\ &=-\frac{\pi}{4}+C=0 \end{align*} t→0limf(t)=t→0lim−∫01[y2+1e−t2(y2+1)]dy+C=−∫01y2+11dy+C=−4π+C=0
所以 C = π / 4 C=\pi/4 C=π/4
f ( t ) = − ∫ 0 1 [ e − t 2 ( y 2 + 1 ) y 2 + 1 ] d y + π 4 f(t)=-\int^1_0\left[\frac{e^{-t^2(y^2+1)}}{y^2+1}\right]\mathcal{d}y+ \frac{\pi}{4} f(t)=−∫01[y2+1e−t2(y2+1)]dy+4π
lim t → ∞ f ( t ) = 0 + π 4 \lim_{t\rightarrow\infty}f(t)=0+\frac{\pi}{4} t→∞limf(t)=0+4π
∫ 0 ∞ e − x 2 d x = π 2 \int^\infty_0e^{-x^2}\mathcal{d}x=\frac{\sqrt{\pi}}{2} ∫0∞e−x2dx=2π